(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
The article describes the social psychological characteristics of the formation of life values in students. It is emphasized that the study of the formation of the personal value system is one of the urgent tasks of modern psychology. During the research, it was found that the values of students are primarily focused on hedonistic, material and family values, and the status of spiritual, moral and aesthetic values is low.